Boosting reverse water-gas shift reaction activity of Pt nanoparticles through light doping of W. Issue 28 (7th July 2021) - Kobayashi, Daiya; Kobayashi, Hirokazu; Kusada, Kohei; Yamamoto, Tomokazu; Toriyama, Takaaki; Matsumura, Syo; Kawaguchi, Shogo; Kubota, Yoshiki; Haneda, Masaaki; Aspera, Susan Meñez; Nakanishi, Hiroshi; Arai, Shigebumi; et al.
Abstract : We report PtW solid-solution alloy nanoparticles (NPs) as a reverse water-gas shift (RWGS) reaction catalyst for the first time. Atomic-level alloying of Pt and W significantly enhanced the RWGS reaction activity of Pt NPs. Abstract : The reverse water-gas shift (RWGS) reaction is an important reaction from the viewpoint of converting CO2 into CO as an important raw material compound. As the RWGS reaction is a mildly endothermic and competitive reaction with CO2 methanation, it is important to improve the activity at low temperatures. Here, we report PtW nanoparticles (NPs) supported on γ-Al2 O3 (PtW NPs/Al2 O3 ) in which Pt and W were randomly mixed for obtaining a highly active and selective catalyst for the RWGS. At low temperatures of 200 and 300 °C, PtW NPs/Al2 O3 exhibited 16- and 17-times higher activity than Pt/Al2 O3, one of the most promising catalysts. The enhanced activity of PtW NPs originated from alloying Pt with W, which contributes to the sintering resistance of Pt NPs, and promotion of CO2 adsorption and CO desorption on the catalyst. Furthermore, PtW NPs/Al2 O3 exhibited high durability and excellent catalytic performance.